Inhibitory Receptor Crosslinking Quantitatively Dampens Calcium Flux Induced by Activating Receptor Triggering in NK Cells - Ganesan, Sridharan; Höglund, Petter (Frontiers in Immunology, 2019)
Natural killer (NK) cell function is regulated by a balance between activating and inhibitory receptors, but the details of this receptor interplay are not extensively understood. We developed a flow cytometry-based assay system in which Ca2+ flux downstream of antibody-mediated activating receptor triggering was studied in the presence or absence of inhibitory receptor co-crosslinking. We show that the inhibitory influence on activating receptor-induced Ca2+ flux is quantitatively regulated, both on murine and human NK cells. Furthermore, both activating and inhibitory receptors operate in an additive way, suggesting that a fine-tuned balance between activating and inhibitory receptors regulate proximal NK cell signalling. We also demonstrate that murine NK cell expression of H2Dd lowered the capacity of Ly49A to deliver inhibitory signals after antibody crosslinking, suggesting that the cis interaction between H2Dd and Ly49A reduce the signalling capacity of Ly49A in this setting. Finally, we show that priming of NK cells by IL-15 rapidly augments Ca2+ flux after activating receptor signalling without attenuating the potential of inhibitory receptors to reduce Ca2+ flux. Our data shed new light on NK cell inhibition and raises new questions for further studies.